2020
DOI: 10.1021/acsanm.0c00159
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of Bacterial Cellulose Nanofibrils and Zein Nanoparticles for Food Packaging

Abstract: The pursuit of sustainable high-performance nanocomposite materials requires the development of nanoscale building blocks based on natural renewable resources and efficient facile production methods. Here, we show a simple, fast, and environmentally friendly route to construct a mechanically robust and multifunctional nanocomposite by using bacterial cellulose nanofibrils (BCNs) and protein zein nanoparticles (ZNs) as natural building blocks. The nanoparticles ZN are successfully incorporated into the BCN netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 56 publications
(134 reference statements)
0
19
0
Order By: Relevance
“…Also, nanotechnology was used for sustainable food packaging. It included blending curcumin with sodium caseinate‐mixed zein nanoparticles (L. Wang et al., 2019), adding gelatin‐kappa‐carrageenan with thymol and zein nanoparticles (Maroufi et al., 2021), zein films added with chitosan nanoparticles and pomegranate‐peel extract (Cui et al., 2020), plasma‐treated zein–catechin–β${{\beta}}$‐cyclodextrin nanocomposite films incorporated with cellulose nanocrystals (L. Jiang et al., 2021), and cellulose nanofibrils mixed with zein nanoparticles as nanocomposites (Q. Li et al., 2020).…”
Section: Protein‐based Polymers For Food Packagingmentioning
confidence: 99%
“…Also, nanotechnology was used for sustainable food packaging. It included blending curcumin with sodium caseinate‐mixed zein nanoparticles (L. Wang et al., 2019), adding gelatin‐kappa‐carrageenan with thymol and zein nanoparticles (Maroufi et al., 2021), zein films added with chitosan nanoparticles and pomegranate‐peel extract (Cui et al., 2020), plasma‐treated zein–catechin–β${{\beta}}$‐cyclodextrin nanocomposite films incorporated with cellulose nanocrystals (L. Jiang et al., 2021), and cellulose nanofibrils mixed with zein nanoparticles as nanocomposites (Q. Li et al., 2020).…”
Section: Protein‐based Polymers For Food Packagingmentioning
confidence: 99%
“…Besides, they showed that the KGM/Zein/Cur composite nanofibril film exhibited excellent antibacterial effects on Escherichia coli and Staphylococcus aureus with a large halo inhibition zone of 12–20 mm (Wang et al ., 2019 ). Besides, some other studies reported that zein‐based composite film loaded with thymol (Li et al ., 2020a , 2020b ), Lauroyl‐L‐arginine ethyl ester monohydrochloride (LAE) (Kashiri et al ., 2019 ) and other antibacterial agents inhibited the growth of microbes. In addition, the combination with essential oil antibacterial agents, there are also many studies on the combination of zein and plant extracts.…”
Section: Protein‐based Antibacterial Materials and Application In Foodmentioning
confidence: 99%
“…In addition, the combination with essential oil antibacterial agents, there are also many studies on the combination of zein and plant extracts. For instance, li and his colleagues (Li et al ., 2020a , 2020b ) developed antimicrobial protein films by using resveratrol (R) and gelatin/zein (GA/ZN). The fibre mats could extend the pork meat shelf life, showing the good application prospect in food preservation.…”
Section: Protein‐based Antibacterial Materials and Application In Foodmentioning
confidence: 99%
“…Based on structure and solubility, it can be divided into α-zein, β-zein, γ-zein and δ-zein [ 2 ]. Due to its excellent self-assembly properties, good biocompatibility and degradability, zein can be used to prepare edible gel particles [ 3 ]. In recent years, zein gel particles have been widely used as carriers for hydrophobic nutrients, including curcumin [ 4 ], beta-carotene [ 5 ], resveratrol [ 6 ], and tocopherol [ 7 ], especially in fat-free or fat-reduced food systems.…”
Section: Introductionmentioning
confidence: 99%